IMPLICATION OF BUSINESS PARTNERSHIP ON THE IMPROVEMENT OF LOCAL BUSINESS IN MANADO - Walean, Enjelia E.; Saerang, David P. E.; Wangke, Shinta J. C. (Universitas Sam Ratulangi, 2021)
Business partnership nowadays keep involving and become one of the important role in determining business success, by conducting a business partnership both parties can further expand their respective businesses. In Manado business partnership already done by many owners of local businesses; in this case the partnership between SMEs and Gojek. This research aims to analyze how business partnership with Gojek affect the improvement ofÂ SMEs in Manado. This research using qualitative method with in-depth interview to collect the data. The samples in this research are 20 owners of SMEs from food and beverages sector in Manado. The result showed business partnership with Gojek has a significant influence on SMEs improvement in Manado. Proven by their statement that their business improved by this partnership, however not all of them have significant improvement. This study suggested that those entrepreneurs need to concern more on what factor that can make this partnership give a significant improvement on their business, also for the government to concern about the existence and the longevity of this business partnership.Â Keywords: Business Partnership, SMEs, Business Performance